Differences in bacteria nanomotion profiles and neutrophil nanomotion during phagocytosis - Pleskova, Svetlana Nikolaevna; Lazarenko, Ekaterina Vladimirovna; Bezrukov, Nikolay Alexandrovich; Bobyk, Sergey Zenonovich; Boryakov, Alexey Vladimirovich; Kriukov, Ruslan Nikolaevich (Frontiers in Microbiology, 2023)
The main goal of this work is to highlight the connection between nanomotion and the metabolic activity of living cells. We therefore monitored the nanomotion of four different clinical strains of bacteria (prokaryotes) and the bacterial phagocytosis by neutrophil granulocytes (eukaryotes). All clinical strains of bacteria, regardless of their biochemical profile, showed pronounced fluctuations. Importantly, the nature of their nanomotions was different for the different strains. Flagellated bacteria (Escherichia coli, Proteus mirabilis) showed more pronounced movements than the non-flagellated forms (Staphylococcus aureus, Klebsiella pneumoniae). The unprimed neutrophil did not cause any difference in cantilever oscillations with control. However, in the process of phagocytosis of S.aureus (metabolically active state), a significant activation of neutrophil granulocytes was observed and cell nanomotions were maintained at a high level for up to 30 min of observation. These preliminary results indicate that nanomotion seems to be specific to different bacterial species and could be used to monitor, in a label free manner, basic cellular processes.